2017
DOI: 10.1186/s13756-017-0277-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing and analysis of the first spontaneous Nanosilver resistant bacterium Proteus mirabilis strain SCDR1

Abstract: Background P. mirabilis is a common uropathogenic bacterium that can cause major complications in patients with long-standing indwelling catheters or patients with urinary tract anomalies. In addition, P. mirabilis is a common cause of chronic osteomyelitis in Diabetic foot ulcer (DFU) patients. We isolated P. mirabilis SCDR1 from a Diabetic ulcer patient. We examined P. mirabilis SCDR1 levels of resistance against Nanosilver colloids, the commercial Nanosilver and silver containing bandages and commonly used … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 91 publications
1
16
0
Order By: Relevance
“…Both our studied strains are located in BB2000-like group; however, K1609 is closely related to BB2000 comparing with the K670. The divergence into two clades represented by BB2000 and HI4320 was previously shown by the phylogenetic analysis using 16S rRNA gene [ 25 ]. Genome of K1609 clusters with the BB2000, BC11–24 and GN2, meanwhile K670 clusters with the AR_0029, AR379 and AR_0155.…”
Section: Resultsmentioning
confidence: 99%
“…Both our studied strains are located in BB2000-like group; however, K1609 is closely related to BB2000 comparing with the K670. The divergence into two clades represented by BB2000 and HI4320 was previously shown by the phylogenetic analysis using 16S rRNA gene [ 25 ]. Genome of K1609 clusters with the BB2000, BC11–24 and GN2, meanwhile K670 clusters with the AR_0029, AR379 and AR_0155.…”
Section: Resultsmentioning
confidence: 99%
“…However, P. mirabilis SCDR1 isolated from a diabetic ulcer presented resistance against commercial Nanosilver products. Pathogenomics analysis showed that this strain carries several mechanisms related to biofilm formation, mobility, active transport and other detoxification methods, which may induce the observed resistance [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, over the last years, a growing body of research has evidenced that bacteria can indeed evolve defense strategies to cope with metallic NPs ( Figure 1B). Bacteria with increased resistance to Ag + ions and Ag-NPs have been repeatedly isolated from clinical and non-clinical environments [46][47][48]. More importantly, different researchers have recently proven that resistance to Ag-NPs or Cu-NPs can be quickly induced in vitro in both laboratory and clinical strains after repeated exposure to sublethal doses of NPs.…”
Section: Bacterial Resistance Mechanisms Towards Metallic Nanoparticlesmentioning
confidence: 99%